Analysis of Sport Tourism Development on Tourism Attractions in Lubuk Linggau, South Sumatra - Muhammad Iqbal Djohan; Suhairi Hazisma; Yayan Dian Fitriansyah (Politeknik Pariwisata Palembang, 2021)
The study aims to discover the development of sport tourism in Lubuk Linggau, South Sumatra. The study uses qualitative method in which data gathered using interview, observation and documentation. The data is analyzed using SWOT. The result shows that although the potential of sport tourism in Lubuk Linggau is very good, but there are some factors that make it hard to develop. Those three factors are the lack of good human resource in tourism, the inability for the local government to cooperate with other parties in pentahelix, and the inability to make an attractive packaging for the market. Therefore, it is suggested to develop a better access to tourism destinations and to improve the skills of tourism human resource as well as to improve the tourism-based services and increase its marketing.